The Implementation of Amtsilati Learning Method to Improve the Ability of Reading Kitab Kuning in the Amtsilati Class Group at Bustanu 'Usyyaqil Qur'an Elementary School Betengan Demak - Musawamah, Mualamatul (Lembaga Pendidikan Hikmatun Najah Blora, 2023)
The aim of this study is to reveal the implementation of Amtsilati learning method in improving the ability of reading Kitab Kuning in the Amtsilati group class at Bustanu 'Usysyaqil Qur'an Betengan Demak Elementary School. This research used a qualitative approach with data collection techniques using interview, observation and documentation. The results showed that the implementation of the Amstilati learning method at SD BUQ Demak included: learning planning, including: objectives, methods, materials, media, evaluation. teaching preparation, preliminary activities, core activities, closing activities. While the learning process in practical classes in improving the ability to read Kitab Kuning is carried out by conducting tests with very good results. Evaluation of learning includes: daily evaluation, volume increase evaluation, midterm evaluation, end of semester evaluation. While the evaluation for practical classes is carried out mid-semester daily and written and oral tests that have met the KKM.